Cerebrospinal fluid phosphorylated tau interacts with MMP2 and MMP3: Associations with cognitive performance in older adults: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Meier, Shelby E.; Khan, Omair A.; Liu, Dandan; Bown, Corey W.; Moore, Elizabeth E.; Pechman, Kimberly R.; Acosta, Lealani Mae Y.; Bell, Susan P.; Blennow, Kaj; Zetterberg, Henrik; Gifford, Katherine A.; Hohman, Timothy J.; et al.
Abstract: Background: Matrix metalloproteinases (MMPs) are enzymes that facilitate extracellular matrix remodeling. In Alzheimer's disease (AD), the MMP system becomes dysregulated and may contribute to disease pathophysiology; however, limited work has examined clinical consequences of MMPs. Thus, we investigated cerebrospinal fluid (CSF) MMP2, MMP3, and MMP9 concentrations in relation to cognitive performance as well as the interaction between MMPs and AD core neuropathology (CSF amyloid beta (Aβ42 ) and phosphorylated tau (p‐tau)) on cognitive outcomes. Methods: Vanderbilt Memory and Aging Project participants free of clinical dementia underwent fasting lumbar puncture for CSF acquisition and neuropsychological assessment (n=153, 73±7 years, 67% male). CSF samples were analyzed in batch using commercially available ELISAs. Linear regression models individually related CSF MMP levels to neuropsychological performance, adjusting for age, sex, race/ethnicity, education, cognitive diagnosis, Framingham Stroke Risk Profile, and apolipoprotein E ( APOE )‐ε4 carrier status. Models were repeated with CSF Aβ42 and p‐tau concentrations as interaction terms. Results: Increased CSF MMP9 related to worse language (p‐values<0.03) and episodic memory performances (p=0.03); however, CSF MMP2 and MMP3 main effects were null (p‐values>0.07). CSF Αβ42 did not interact with MMP2, MMP3, or MMP9 concentrations on any neuropsychological outcome (p‐values>0.09). By contrast, CSF p‐tau interacted with CSF MMP2 and MMP3 levels on language performance (p‐values<0.02), and CSF p‐tau interacted with CSF MMP2 levels on episodic memory performance (p=0.01). Increased CSF MMP2 and MMP3 associations with worse language and episodic memory performances were driven by p‐tau negative participants, whereas (unexpectedly) increased CSF MMP2 was associated with better language performance among p‐tau positive participants. Conclusion: Among older adults without clinical dementia or stroke, increased CSF MMP9 related to worse cognitive performance, suggesting extracellular matrix remodeling may be one pathway underlying the development of cognitive impairment. CSF p‐tau, but not Αβ42, interacted with MMP2 and MMP3 concentrations on cognitive performance. P‐tau may interact with MMPs on clinical expression of pathology in complex ways, such that increased CSF levels of MMPs may only be associated with worse cognition in non‐demented older adults in the absence of concomitant neuropathology. Funding: Alzheimer's Association IIRG‐08‐88733, R01‐AG034962, R01‐AG056534, K24‐AG046373.